Establishing an Orchid Conservation Alliance - Tobias, Peter (Universidad de Costa Rica, 2015)
Almost every orchid society and orchid grower realizes that orchids in the wild are in danger of dis- appearing. The simple growth of the human popula- tion dictates that spaces that once were subject only to the vagaries of nature are now impacted by the human need for space to live and grow food. As orchid lovers, what can we do ?